2006
DOI: 10.1021/jf051988p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tea Polyphenols on Emulsification of Olive Oil in a Small Intestine Model System

Abstract: Tea catechins have been shown to reduce plasma cholesterol and suppress hypertriacylglycerolemia by reducing triglyceride absorption. However, the mechanism is not yet clear. One of the possible mechanisms is that tea polyphenols may modify dietary fat emulsification in the gastrointestinal tract. The digestive enzyme (lipase) acts on specific emulsion interface properties (droplet size and surface area). Therefore, changes in these properties may modify emulsification and lead to changes in dietary fat digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 36 publications
3
99
0
2
Order By: Relevance
“…Different studies have been carried out into the interaction between polyphenols and a food matrix such as milk (23,24) , olive oil (25) or sugar (26) . The evidence suggests that variations in polyphenol absorption also occur due to * Corresponding author: Dr Maria-José Motilva, fax þ34 973 702596, email motilva@tecal.udl.es Abbreviations: GSPE, grape seed procyanidin extract; IN, fraction found inside dialysis solution; OUT, fraction found outside dialysis solution; PC, procyanidins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have been carried out into the interaction between polyphenols and a food matrix such as milk (23,24) , olive oil (25) or sugar (26) . The evidence suggests that variations in polyphenol absorption also occur due to * Corresponding author: Dr Maria-José Motilva, fax þ34 973 702596, email motilva@tecal.udl.es Abbreviations: GSPE, grape seed procyanidin extract; IN, fraction found inside dialysis solution; OUT, fraction found outside dialysis solution; PC, procyanidins.…”
mentioning
confidence: 99%
“…Different studies have been carried out into the interaction between polyphenols and a food matrix such as milk (23,24) , olive oil (25) or sugar (26) . The evidence suggests that variations in polyphenol absorption also occur due to interactions between polyphenols and other food components.…”
mentioning
confidence: 99%
“…Furthermore, green tea extract (32) and oolong tea polyphenols (33) are known to have lipase inhibitory activity. Shishikura et al (34) have reported the possibility that lipid absorption is suppressed by minimal ingestion of polyphenols. Sugiyama et al (18) also suggest that the small intestine inhibits absorption, which leads to the increased production of fecal bile acid.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wang et al, the increasing of lipase inhibitory activity with catechins depended on the ratio of catechins to lipase and reach to the limit at the constant level 15 . Furthermore, lipase activity was also influenced by the emulsion particle size, which was determined by a number of factors such as mineral and emulsifier levels 21 . Therefore, the EEX-mediated inhibition of lipase might be suppressed by the catechin:lipase ratio and the level of emulsification.…”
Section: Discussionmentioning
confidence: 99%